Research on the Impact of Venture Capital on Regional Technological Innovation Performance - Han, Peizhe (Education Insights, 2026)
China’s economy is currently undergoing a transformation and upgrading phase aimed at enhancing quality and efficiency. The growth model has shifted from extensive factor-driven growth to innovation-driven development. However, existing innovation capabilities still fall short of meeting the requirements for high-quality economic development. The 14th Five-Year Plan and the foreseeable future have imposed more urgent and higher demands on regional innovation. Under the new development paradigm, how to leverage comparative advantages in industries and technologies based on regional resource endowments, and implement regional coordinated development strategies, has become a pressing issue. Given the high costs, risks, and long investment cycles associated with technological innovation, traditional financial institutions often fail to meet funding needs. Ensuring stable funding sources for innovation activities is therefore crucial, with venture capital being recognized as a vital external funding channel. This study focuses on the impact of venture capital on regional technological innovation performance. Through data collection and analysis, an empirical model was constructed to explore their relationship. The findings demonstrate that venture capital plays a positive and significant role in improving regional technological innovation performance, though its effects vary across different regions. This research provides theoretical foundations and practical references for formulating rational innovation policies and attracting venture capital in regional development.